Kozmetični izdelki za zaščito kože pred okoljskimi onesnaževali - Zvonar Pobirk, Alenka (Farmacevtski vestnik, 2023)
Lately, anti-pollution cosmetic products are experiencing significant growth and many cosmetic products on the market claim anti-pollution effects due to increasing levels of pollutants in many metropolitan areas around the world. Constant exposure to air pollution is associated with detrimental effects on the skin by causing oxidative stress and inflammation, leading to premature ageing and aggravation of inflammatory skin diseases such as acne, atopic dermatitis and psoriasis among others. This review presents various strategies of anti-pollution (cosmetic) products – from preventing pollutants deposition on the skin and strengthening skin barrier function to decreasing oxidative stress and reducing inflammation, as well as in vivo/in vitro efficacy testing for anti-pollution claims.
Keywords: Kozmetika; Koža; kožna bariera; mehanizmi delovanja; Okolje; okoljska onesnaževala; vrednotenje in vivo/in vitro; zaščitni izdelki